Meropenem–Vaborbactam Pharmacokinetics in Subjects with Chronic Renal Impairment, Including Hemodialysis. (4th October 2017) - Rubino, Christopher M; Griffith, David C; Bhavnani, Sujata M; Loutit, Jeffrey S; Lohse, Brooke; Dudley, Michael N; Ambrose, Paul G
Abstract: Background: Vaborbactam is a member of a new class of β-lactamase inhibitors with inhibitory activity against important β-lactamases, particularly serine carbapenemases, and is being developed in combination with meropenem. The combination is highly active against gram-negative pathogens, especially KPC-producing, carbapenem-resistant Enterobacteriaceae. This report describes the pharmacokinetic data of the combination in subjects with chronic renal impairment, including hemodialysis. Methods: A total of 41 subjects were enrolled in a Phase 1 study and assigned to one of five groups based on renal function. Subjects were classified as having mild, moderate, or severe renal impairment if they had an estimated glomerular filtration rate (eGFR) of 60 to 89, 30 to <60, or <30 mL/minute/1.73 m 2, respectively. Normal renal function was defined as an eGFR ≥90 mL/minute/1.73 m 2 . Subjects with end stage renal disease (ESRD) who were receiving hemodialysis therapy 3 times a week for at least 3 months prior to Day 1 of the study were the final group. All subjects received a single IV dose of meropenem 1 g–vaborbactam 1 g in combination as a 3-hour infusion. Subjects were dosed on Day 1 with the exception of the ESRD group that received two doses (On- and Off-dialysis) separated by a washout. Plasma samples were assayed for meropenem and vaborbactam using validated HPLC/MS methods; total plasma clearance (CLt) was estimated by standard non-compartmental methods. Results: Meropenem and vaborbactam CLt were similar and both drugs are removed by hemodialysis (table). Meropenem and vaborbactam CLt decreased with decreasing renal function and the slopes of the relationships between eGFR and CLt were similar (figure), indicating a similar proportional reduction in CLt with decreasing renal function. Conclusion: These data suggest that dose reduction in subjects with renal impairment should be similar for both meropenem and vaborbactam. Disclosures: C. M. Rubino, The Medicines Company: Research Contractor, Research support; D. C. Griffith, The Medicine's Company: Employee and Shareholder, Salary; S. M. Bhavnani, The Medicines Company: Research Contractor, Research support; J. S. Loutit, The Medicine's Company: Employee and Shareholder, Salary; B. Lohse, The Medicines Company: Employee, Salary; M. N. Dudley, The Medicine's Company: Employee and Shareholder, Salary; P. G. Ambrose, Paratek Pharmaceuticals: Research Contractor, Research support.